The contribution of recently identified adult BMI risk loci to paediatric obesity in a Singaporean Chinese childhood dataset. Issue 6 (25th October 2016) - Dorajoo, R.; Ong, R. T‐H.; Sim, X.; Wang, L.; Liu, W.; Tai, E. S.; Liu, J.; Saw, S‐M.
Summary: Introduction: Recent genome‐wide association studies have identified 103 adult obesity risk loci; however, it is unclear if these findings are relevant to East‐Asian childhood body mass index (BMI) levels. Methods and Results: We evaluated for paediatric obesity associations at these risk loci utilizing genome‐wide data from Chinese childhood subjects in the Singapore Cohort study Of the Risk factors for Myopia study ( N  = 1006). A weighted gene‐risk score of all adult obesity risk loci in the Singapore Cohort study Of the Risk factors for Myopia study showed strong associations with BMI at age 9 ( p ‐value = 3.40 × 10 −12 ) and 4‐year average BMI (age 9 to 12, p ‐value = 6.67 × 10 −8 ). Directionally consistent nominal associations for 15 index single nucleotide polymorphisms (SNPs) ( p ‐value < 0.05) were observed. Pathway analysis with genes from these 15 replicating loci revealed over‐representation for the G‐protein‐coupled receptor (GPCR)‐mediated integration of entero‐endocrine signalling pathway exemplified by L‐cell (adjusted p ‐value = 0.018). Evaluations of birth weight to modify the effects of BMI risk SNPs in paediatric obesity did not reveal significant interactions, and these SNPs were generally not associated with birth weight. Conclusions: At least some common adult BMI risk variants predispose to paediatric obesity risk in East‐Asians.